Analysis of the Influence of Digital Social Media Literacy on the Performance of Agricultural Extension Workers in Muara Enim Regency, South Sumatra Province - Sutami Sutami; Yudhi Zuriah Wirya Purba; Eka Thanomutiara (Journal of Science and Science Education, 2025)
This study aims to analyze the influence of social media use on the performance of agricultural extension workers in Muara Enim Regency, as well as to examine the role of digital literacy as a moderating variable. The research was conducted from April to June 2025 using a quantitative approach and an explanatory method. The study population consisted of all active agricultural extension workers in Muara Enim Regency, both civil servants and non-civil servants, totaling 195 individuals. Based on the Slovin formula with a 5% margin of error, a sample of 131 respondents was obtained, considered representative of the population characteristics. Data were collected through a Likert-scale questionnaire (1–5), supported by documentation and observation, and then analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with the aid of SPSS 26. The results show that simultaneously all independent and moderating variables significantly influence the performance of extension workers. Partially, information and communication technology (ICT) competence (X2), personal innovation (X3), and organizational support (X4) have a positive and significant effect on performance. Meanwhile, social media use (X1) and digital literacy (Z) do not have a direct significant effect. However, digital literacy is proven to play a significant moderating role in strengthening the relationship between social media use, ICT competence, and organizational support with the performance of extension workers. Thus, digital literacy is a crucial factor in optimizing the utilization of digital technology to support the improvement of agricultural extension workers’ performance